GREEN ECONOMY: THE ECONOMIC BASIS OF ECOLOGICALLY SUSTAINABLE DEVELOPMENT - Umida Xaybiyeva (Modern American Journals, 2025)
This article examines the concept of the green economy as the economic foundation for achieving ecological sustainability. It emphasizes that the green economy represents a strategic shift from traditional models of growth toward environmentally responsible development that integrates economic, social, and ecological priorities. The study analyzes the relationship between green economic policies and sustainable growth, highlighting the potential of renewable energy, energy efficiency, waste minimization, and sustainable agriculture to drive long-term prosperity. The research also explores the efforts undertaken in the Republic of Uzbekistan to develop a green economy within the context of global environmental challenges and the transition toward low-carbon development. Theoretical and empirical materials from international organizations such as UNEP, OECD, and the World Bank are used to evaluate green growth indicators and their implications for developing countries. The study concludes that the green economy is not merely an environmental policy but a comprehensive strategy for ensuring economic competitiveness, social welfare, and environmental resilience.
Keywords: Green economy, sustainable development, renewable energy, green growth, environmental policy, energy efficiency, innovation, investment, low-carbon development, green finance.